OUT OF POOLS: MOVEMENT PATTERNS OF MEDITERRANEAN STREAM FISH IN RELATION TO DRY SEASON REFUGIA. (28th May 2014) - Pires, D. F.; Beja, P.; Magalhães, M. F.
ABSTRACT Movement may critically influence population persistence in the face of disturbance. However, data on individual movements into and out of refugia in response to disturbance remain limited, leading to an incomplete understanding of the ecological significance of mobility. Using individually marked chubs Squalius torgalensis in a seasonally drying Mediterranean stream, we quantified the rate, direction and magnitude of movements out of dry season pools, and of movements displayed across the stream over the period of hydrological connection. Recapture rate was lower in individuals marked in dry season pools (3.3%; n = 894) than in individuals marked during hydrological connection (13.0%; n = 522). Nearly half the recaptures (46.7%; n = 30) of chubs marked in dry season pools corresponded to movements that were generally longer than 100 m, overpassing the average distance among isolated pools. The frequency and distances travelled out of dry season pools were similar in upstream and downstream directions. Only 20.6% of recaptures of individuals marked during hydrological connection corresponded to movements, with more frequent and larger movements in the upstream direction. Body size was related to movement probability only for chubs marked during hydrological connection. Our results highlight considerable individual variability in movement and underscore the importance of understanding the consequences of this variation and how it may be maintained in fish populations facing increasing fragmentation and intermittency of riverscapes. Copyright © 2014 John Wiley & Sons, Ltd.